2011
DOI: 10.1017/s1755048311000186
|View full text |Cite
|
Sign up to set email alerts
|

Identity, Attitudes, and the Voting Behavior of Mosque-Attending Muslim-Americans in the 2000 and 2004 Presidential Elections

Abstract: In a post-September 11 world, no religious group in the United States has become more important yet remains more misunderstood than Muslim-Americans. This is particularly true with respect to the manner in which religious and political attitudes influence Muslim-Americans’ political behavior. This article addresses this issue by using data gathered from surveys taken in 70 mosques throughout the United States. With these data, this article maps the political and religious attitudes and behavior of mosque-atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Research on the general public during this span has elaborated both policy preference and affect toward American Muslims (Davis and Silver 2004; Huddy et al 2005; Davis 2007; Kalkan, Layman, and Uslaner 2009; Sides and Gross 2013). Relatedly, a smaller set of empirical studies have examined the attitudes and behaviors of American Muslims themselves, highlighting the dynamics of alienation and political incorporation within this community (Jamal 2005; Ayers and Hofstetter 2008; Patterson, Gasim, and Choi 2011; Oskooii 2015; Read 2015). Our project is situated in this latter, still nascent branch of the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the general public during this span has elaborated both policy preference and affect toward American Muslims (Davis and Silver 2004; Huddy et al 2005; Davis 2007; Kalkan, Layman, and Uslaner 2009; Sides and Gross 2013). Relatedly, a smaller set of empirical studies have examined the attitudes and behaviors of American Muslims themselves, highlighting the dynamics of alienation and political incorporation within this community (Jamal 2005; Ayers and Hofstetter 2008; Patterson, Gasim, and Choi 2011; Oskooii 2015; Read 2015). Our project is situated in this latter, still nascent branch of the literature.…”
mentioning
confidence: 99%
“…Second, in addition to building on the relative dearth of research American Muslims, this study highlights the disparate ways in which key determinants influence political behavior within this community's subgroups. Whether due to the difficulty in obtaining a sizeable sample from this relatively small population (Patterson, Gasim, and Choi 2011; Djupe and Calfano 2012), 2 or simply an implicit decision to limit the analysis to inferences about the sample as a whole (Ayers and Hofstetter 2008; Jalalzai 2009), studies of American Muslim political attitudes and behavior conditioned on key demographic distinctions is, not surprisingly, quite rare (see below for exceptions to this general rule). Altogether absent, however, is a comprehensive assessment of the differential effects attendant to these distinctions.…”
mentioning
confidence: 99%
“…When asked if the United States-led war on terrorism was a sincere effort to reduce international terrorism, the majority of Muslims in the United States said it was not (55.0 percent) (Pew Research Center 2007, 49), thought this fell to 41.0 percent in 2011. In a survey of Muslim-Americans, Patterson, Gasim and Jangsup (2011, 9) also found that few supported the war in Iraq. Moreover, when asked if the Iraq War was important for the security of the United States, more than 90 percent disagreed.…”
Section: Minority Groups and Public Opinion Towards Foreign Policy Ismentioning
confidence: 99%
“…Moreover, when asked if the Iraq War was important for the security of the United States, more than 90 percent disagreed. Muslim-Americans were generally in agreement that their civil rights have suffered since the attacks of September 11 (Patterson, Gasim and Jangsup 2011, 9).…”
Section: Minority Groups and Public Opinion Towards Foreign Policy Ismentioning
confidence: 99%
“…On the other hand, it is also true that mosque‐attending Muslim Americans in our sample were a very diverse group, hailing from many different countries and representing many ethnicities . As a result, they may bring different ethnic and cultural sensibilities to issues of politics and, thus, may not respond in a uniform manner (Patterson, Gasim, and Choi ). In addition to this, in post‐9/11 America, it may be that the more religiously committed Muslim Americans choose to withdraw from noticeable political activities, leading to the opposite relationship between religious commitment and political participation.…”
Section: Religion and Political Participationmentioning
confidence: 99%